Penatalaksanaan Fisioterapi pada Kasus Pre Operative Canal Stenosis akibat Spondylolisthesis Vertebra Lumbal IV dan V di RSUD Dr. Soetomo Surabaya - Ayuni, Azzahro Qurratan; , Totok Budi Santoso, M.Fis, MPH (2016)
Background : Canal stenosis describes a stenotic of foramen vertebrale on one or more vertebrae one of which can be caused by any condition such us spondylolisthesis. Spondylolisthesis is translation of corpus vertebra to it's under. Modality, which can be given in such cases is a therapeutic exercise in the form of Deep Breathing Exercise, Active Range of Motion, Manual Resistance Exercise, Mc. Kenzie Exercise dan Core Stability Exercise. Objective : To determine wether therapeutic exercise can reducing pain, increasing muscle strength, range of motion and functional capabilities. Results : After four times treatments showed their silent pain reduction from 2,6 cm to 2,3 cm , tenderness of 4 cm to 3,7 cm and painful motion of 6 cm to 4,5 cm. Increasing strength muscle of flexion trunk of 3 to 4 and the trunk extension from 3 to 4 ,thereis no changes for lower limb strength muscle limb, increasing range of trunk motion moves in flexion of 43 cm to 44 cm, moves the extension from 37 cm to 35 cm, moves the right lateral flexion from 30 cm to 28 cm and moves the left lateral flexion of 43 cm to 42 cm, the improvement alsohappens in functional capabilities, the value is from 54,28 % to 51,428 %. Conclusion : Therapeutic exercise can reduce pain, improving muscle strength, increasing the range of motion and improving functional ability.